Determinants of injuries status among motorcyclists that involved in road accidents in Malaysia / Norhamiza Mohd Feshol - Mohd Feshol, Norhamiza (2015)
The number of motorcyclist involved in road accident which resulted in death or injuries is higher than pillion riders in Malaysia. The aim of this study is to examine whether there exist significant relationship between dependent variable (injuries status) and independent variables ( type of collision, road category, traffic system, road type, type of area, location, fault of motorcyclist, usage of helmet, and part of body injury) and to determine factors ( type of collision, road category, traffic system, road type, type of area, location, fault of motorcyclist, usage of helmet, and part of body injury) significantly influence injuries status. A total 11,260 of motorcyclist accident with death, serious injury and minor injury were analyzed. Other than that, for this study the data was analyzed using Chi-Square test and Multinomial Logistic Regression. The chi-square test is used to discover if there is a relationship between dependent variable and independent while Multinomial Logistic Regression analysis is used to discover if there is significant influence of independent variable on dependent variable. The results showed that there has significant relationship between independent variable (type of collision, road category, traffic system, road type, type of area, location, fault of motorcyclist, usage of helmet, and part of body injury) and dependent variable (injuries status). And there is significant influence independent variable (type of collision, road category, traffic system, road type, type of area, location, fault of motorcyclist, usage of helmet, and part of body injury) on dependent variable (injuries status)